Phorcysia thermohydrogeniphila gen. nov., sp nov., a thermophilic, chemolithoautotrophic, nitrate-ammonifying bacterium from a deep-sea hydrothermal vent - Perez-Rodriguez, Ileana; Grosche, Ashley; Massenburg, Lynnicia; Starovoytov, Valentin; Lutz, Richard A; Vetriani, Costantino (INTERNATIONAL JOURNAL OF SYSTEMATIC AND EVOLUTIONARY MICROBIOLOGY, 2012)
A novel hyperthermophilic, anaerobic, chemolithoautotrophic bacterium, designated strain HB-8(T), was isolated from the tube of Alvinella pompejana tubeworms collected from the wall of an actively venting sulfide structure on the East Pacific Rise at 13 degrees N. The cells were Gram-negative rods, approximately 1.0-1.5 mu m long and 0.5 mu m wide. Strain HB-8(T) grew between 65 and 80 degrees C (optimum 75 degrees C), 15 and 35 g NaCl l(-1) (optimum 30 gl(-1)) and pH 4.5 and 8.5 (optimum pH 6.0). Generation time under optimal conditions was 26 min. Growth occurred under chemolithoautotrophic conditions with H-2 as the energy source and CO2 as the carbon source. Nitrate and sulfur were used as electron acceptors, with concomitant formation of ammonium or hydrogen sulfide, respectively. The presence of lactate, formate, acetate or tryptone in the culture medium inhibited growth. The G+C content of the genomic DNA was 47.8 mol{%}. Phylogenetic analysis of the 16S rRNA gene and of the alpha subunit of the ATP citrate lyase of strain HB-8(T) indicated that this organism formed a novel lineage within the class Aquificae, equally distant from the type strains of the type species of the three genera that represent the family Desulfurobacteriaceae: Thermovibrio ruber ED11/3LLK8(T), Balnearium lithotrophicum 17S(T) and Desulfurobacterium thermolithotrophum BSA(T). The polar lipids of strain HB-8(T) differed substantially from those of other members of the Desulfurobacteriaceae, and this bacterium produced novel quinones. On the basis of phylogenetic, physiological and chemotaxonomic characteristics, it is proposed that the organism represents a novel genus and species within the family Desulfurobacteriaceae, Phorcysia thermohydrogeniphila gen. nov., sp. nov. The type strain of Phorcysia thermohydrogeniphila is HB-8(T) (=DSM 24425(T) =JCM 17384(T)).
Keywords: HOV Alvin (Human Occupied Vehicle)